A tablet-based quantitative assessment of manual dexterity for detection of early psychosis - Le Boterff, Quentin; Rabah, Ayah; Carment, Loïc; Bendjemaa, Narjes; Térémetz, Maxime; Alouit, Anaëlle; Levy, Agnes; Tanguy, Guillaume; Morin, Valentine; Amado, Isabelle; Cuenca, Macarena; Turc, Guillaume; et al. (Frontiers in Psychiatry, 2023)
Background: We performed a pilot study on whether tablet-based measures of manual dexterity can provide behavioral markers for detection of first-episode psychosis (FEP), and whether cortical excitability/inhibition was altered in FEP. Methods: Behavioral and neurophysiological testing was undertaken in persons diagnosed with FEP (N=20), schizophrenia (SCZ, N=20), autism spectrum disorder (ASD, N=20), and in healthy control subjects (N=20). Five tablet tasks assessed different motor and cognitive functions: Finger Recognition for effector (finger) selection and mental rotation, Rhythm Tapping for temporal control, Sequence Tapping for control/memorization of motor sequences, Multi Finger Tapping for finger individuation, and Line Tracking for visuomotor control. Discrimination of FEP (from other groups) based on tablet-based measures was compared to discrimination through clinical neurological soft signs (NSS). Cortical excitability/inhibition, and cerebellar brain inhibition were assessed with transcranial magnetic stimulation. Results: Compared to controls, FEP patients showed slower reaction times and higher errors in Finger Recognition, and more variability in Rhythm Tapping. Variability in Rhythm Tapping showed highest specificity for the identification of FEP patients compared to all other groups (FEP vs ASD/SCZ/Controls; 75% sensitivity, 90% specificity, AUC = 0.83) compared to clinical NSS (95% sensitivity, 22% specificity, AUC=0.49). Random Forest analysis confirmed FEP discrimination vs other groups based on dexterity variables (100% sensitivity, 85% specificity, balanced accuracy=92%). The FEP group had reduced short-latency intra-cortical inhibition (but similar excitability) compared to controls, SCZ, and ASD. Cerebellar inhibition showed a non-significant tendency to be weaker in FEP. Conclusion: FEP patients show a distinctive pattern of dexterity impairments and weaker cortical inhibition. Easy-to-use tablet-based measures of manual dexterity capture neurological deficits in FEP and are promising markers for detection of FEP in clinical practice.